2010
DOI: 10.1021/jo100886p
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Role of Vicinal OH in Ester Aminolysis: Proton Shuttle versus Hydrogen Bond Stabilization

Abstract: This computational study provoked by the process of peptide bond formation in the ribosome investigates the influence of the vicinal OH group in monoacylated diols on the elementary acts of ester aminolysis. Two alternative approaches for this influence on ester ammonolysis were considered: stabilization of the transition states by hydrogen bonds and participation of the vicinal hydroxyl in proton transfer (proton shuttle). The activation due to hydrogen bonds of the vicinal hydroxyl via tetragonal transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…As reported elsewhere [52], the analysis of the Gibbs free energy of activation of different transition states resulted in essentially the same conclusion. In order to evaluate the influence of the polarization and diffuse functions in the basis set of hydrogen atoms, we can compare the calculated energies of different stationary points along the reaction paths obtained with 6-31 + G* and 6-31 + + G** basis sets (Table 2).…”
Section: Comparison Of Different Reaction Pathssupporting
confidence: 79%
See 1 more Smart Citation
“…As reported elsewhere [52], the analysis of the Gibbs free energy of activation of different transition states resulted in essentially the same conclusion. In order to evaluate the influence of the polarization and diffuse functions in the basis set of hydrogen atoms, we can compare the calculated energies of different stationary points along the reaction paths obtained with 6-31 + G* and 6-31 + + G** basis sets (Table 2).…”
Section: Comparison Of Different Reaction Pathssupporting
confidence: 79%
“…This selection of the reagents is not accidental but determined by the presence in the formylethanediol molecule of a vicinal hydroxyl next to the reaction center analogously to the ribose ring in tRNA. As shown in our theoretical investigations of the mechanism for this model reaction (Scheme 1a and b) [17,52], the latter one based on the transition state search reported here, the catalytic role of this vicinal hydroxyl group could be explained by the stabilization of the transition state structures via formation of intramolecular hydrogen bonds (tetragonal transition states in Scheme 1a) or by a direct participation of this vicinal hydroxyl in the proton transfer process (hexagonal transition states in Scheme 1b). Both possible reaction paths are presented in Scheme 1a and b, while the applied notation of the atoms is presented in Scheme 1c on the example of the tetrahedral intermediate I.…”
Section: Search Of Transition State Structuresmentioning
confidence: 64%
“…Recently, computational methods were used to evaluate concerted proton shuttle mechanisms with and without an additional water molecule, and favored a fully concerted eight-member proton shuttle(similar to transition state A) 10 . Alternatively, other computational studies have indicated a stepwise proton shuttle would be favorable 11,12 . All of these possibilities have been proposed 4,813 .…”
mentioning
confidence: 99%
“…The 2′-hydroxyl is important for the ribosome reaction, but the pK a of a hydroxyl dictates that if it abstracts the amino proton it must donate its proton elsewhere. This mechanism, termed the “proton shuttle” has been proposed in a variety of forms for the ribosome 812 . Alternatively, the 2′-hydroxyl may provide an important transition state hydrogen bond, with another group or a water molecule deprotonating the nucleophile.…”
mentioning
confidence: 99%
See 1 more Smart Citation